Bartholomae’s law revisited and remodelled - Šefčík, Ondřej (Lingua Posnaniensis, 2025)
The present paper deals with Bartholomae’s Law in Indo-Iranian languages. After a new examination of the data, it concludes that in the case of Bartholomae’s Law, there is no assumed ʽtransfer of aspiration ʼ or any other similar process but that the attested plosives are the result of a process of plosivization of the original Indo-Iranian voiced fricatives Δ (< IE *Dh). Thus, the process described by Bartholomae is not an exception in developing of plosive clusters but a regular process affecting the original fricatives, plosives in the outcome clusters being of secondary origin.